A high temperature oxidation resistant coating based on titanium alloy substrate self-diffusion and preparation method thereof

By preparing the AlCoCrFeNiTi high-entropy alloy coating on the surface of γ-TiAl alloy, and using the matrix self-diffusion to form Ti elements, the problem of insufficient oxidation resistance in high-temperature environments is solved, and better oxidation resistance and longer service life are achieved.

CN116180013BActive Publication Date: 2025-04-04NANJING UNIV OF AERONAUTICS & ASTRONAUTICS +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202211742743.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-04-04
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The γ-TiAl alloy has insufficient oxidation resistance in high-temperature environments, resulting in the formation of surface oxides and reducing service life.

Method used

AlCoCrFeNiTi high-entropy alloy coating was prepared on the surface of γ-TiAl alloy by using Shuanghui plasma alloying technology. Ti elements were formed through the self-diffusion of the matrix, thereby enhancing the metallurgical bonding between the coating and the matrix.

Benefits of technology

It significantly improves the oxidation resistance of the surface of γ-TiAl alloy under high temperature environments above 800℃, enhances the binding ability of the coating and the substrate, and extends the service life of the workpiece.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116180013B_ABST
    Figure CN116180013B_ABST
Patent Text Reader

Abstract

The present invention discloses a high-temperature oxidation resistant coating based on self-diffusion of a titanium alloy matrix and a preparation method thereof, belonging to the field of metal or alloy surface treatment, wherein the high entropy alloy coating is AlCoCrFeNiTi, and the high entropy alloy coating has a cubic structure and exists in the form of a single solid solution. The present invention adopts double glow plasma alloying technology, uses an AlCoCrFeNi target as a sputtering source, bombards the target with high-purity argon gas, diffuses TiAl alloy matrix elements outward, and prepares an AlCoCrFeNiTi high entropy alloy coating resistant to high-temperature oxidation on its surface. The high entropy alloy coating prepared by the present invention is resistant to oxidation, has high bonding strength, and has good comprehensive mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal or alloy surface treatment, and in particular relates to a high-temperature oxidation resistant coating based on titanium alloy substrate self-diffusion and a preparation method thereof. Background Art

[0002] The rapid development of the aerospace industry has stimulated the emergence of titanium alloys, especially intermetallic compound TiAl alloys, which have good thermal stability. γ-TiAl alloy has a low density (about 4g / cm 3 ), high specific strength and specific stiffness, good high temperature creep and high temperature fatigue properties, etc., and is considered to be a potential weight-saving structural material. However, like many other intermetallic compounds, γ-TiAl alloy has the disadvantages of relative brittleness and poor oxidation resistance. Regarding the former, many scholars have basically met most of the application environments at room temperature by adjusting the chemical composition and microstructure of TiAl alloy. However, after high-temperature treatment, oxides appear on the surface of γ-TiAl alloy, with porous TiO2 and Al2O3 as minority phases, and the corrosion products reduce the service life. In order to improve the high-temperature oxidation resistance of TiAl-based alloys to meet the requirements of aircraft engines, surface modification treatment is required.

[0003] High entropy alloy (HEAs) is an alloy with high mixing entropy, containing more than five main elements. Based on the high entropy effect and hysteresis diffusion effect, HEAs tend to form a simple solid solution structure at high temperature, and the grains are no longer coarsened. Therefore, HEAs materials show good wear resistance, corrosion resistance, and oxidation resistance, becoming a potential surface coating material. AlCoCrFeNi is a high entropy alloy coating that has been studied more. In this system, Ni and Co elements provide good oxidation resistance and ductility for the coating, and Al and Cr mainly affect the oxidation resistance of the coating. In addition, a continuous and dense Al2O3 layer is formed during the oxidation process of Al, which plays a good protective role, and Cr forms Cr2O3 with oxidation resistance. At present, the common methods for preparing high entropy alloy coatings include magnetron sputtering, laser cladding, thermal spraying, etc. The high entropy alloy coatings prepared by these methods have the disadvantages of low bonding strength with the substrate and easy cracking of the coating. Summary of the invention

[0004] The present invention provides a high-temperature oxidation resistant coating based on titanium alloy substrate self-diffusion and a preparation method thereof. An AlCoCrFeNiTi high-entropy alloy coating with metallurgical bonding and high-temperature oxidation resistance is prepared on the surface of a γ-TiAl alloy. The Ti element in the coating is formed by substrate self-diffusion, which improves the high-temperature oxidation resistance of the substrate surface and also enables the coating to have good bonding ability with the substrate, thereby preventing the coating from falling off during service, thereby protecting the workpiece and extending the life of the workpiece.

[0005] To achieve the above objectives, the present invention adopts the following technical solutions:

[0006] A high-temperature oxidation resistant coating based on self-diffusion of a titanium alloy substrate, the coating being an AlCoCrFeNiTi high-entropy alloy coating, the coating comprising a deposition layer and a diffusion layer from the outside to the inside, the elements in the deposition layer being Al, Co, Cr, Fe, Ni and Ti, the elements in the diffusion layer being Al, Co, Cr, Fe, Ni and Ti, the elements Al, Co, Cr, Fe and Ni being diffused from the coating to the substrate, and the element Ti being diffused from the substrate to the coating; the Ti element in the coating originates from the AlCoCrFeNiTi high-entropy alloy coating formed by self-diffusion of a TiAl substrate, the coating thickness being controllable, and the content of the Ti element in the coating being controllable; the deposition layer thickness being 15 to 25 μm, preferably 20 μm; the diffusion layer thickness being 20 to 35 μm, preferably 25 μm.

[0007] A method for preparing a high temperature oxidation resistant coating based on self-diffusion of a titanium alloy substrate comprises the following steps:

[0008] S1: Pre-prepare an AlCoCrFeNiTi pre-infiltration layer on the surface of the γ-TiAl alloy using double glow plasma alloying technology to allow the substrate and the coating to form mutual diffusion to the greatest extent; this is conducive to the formation of metallurgical bonding between the substrate and the coating, improves the bonding strength between the substrate and the coating, and solves the problem of mismatching thermal expansion coefficients between the substrate and the coating to the greatest extent. Then, the pre-infiltration layer is vacuum annealed to promote the diffusion of coating elements in TiAl, generate a stable structure, and enhance bonding strength;

[0009] S2: Double glow plasma alloying technology is used in the pre-infiltrated AlCoCrFeNiTi layer. By changing the workpiece pole and target pole parameters, the matrix Ti diffusion is achieved, and the Ti content is controllable, which can not only improve the mechanical properties of the matrix, but also solve the problem of excessive Ti diffusion affecting the high temperature oxidation resistance of the coating, and prepare AlCoCrFeNiTi high entropy alloy high temperature oxidation resistant coating.

[0010] In the above steps, the preparation of the AlCoCrFeNiTi pre-infiltration layer in step S1 includes the following steps:

[0011] (1) Set the workpiece voltage to 400 V and the target voltage to 900 V; (2) Adjust the workpiece duty cycle, adjust the workpiece temperature to 800°C to 1000°C, and keep it warm for 3 h to 7 h; (3) The annealing temperature is 600°C to 900°C, and the annealing time is 2 to 10 hours.

[0012] Preferably, the workpiece temperature is 850° C., the holding time is 3 hours, and the vacuum annealing is 4 hours.

[0013] The preparation of the AlCoCrFeNiTi high entropy alloy layer in step S2 specifically includes the following steps: (1) maintaining the workpiece voltage at 400 V and reducing the target voltage to 800 V; (2) adjusting the workpiece duty cycle, adjusting the workpiece temperature to 700°C to 900°C, and the insulation time to 5h to 7h.

[0014] Preferably, the workpiece temperature is 750° C. and the insulation time is 5 hours.

[0015] The present invention provides application of the above-mentioned AlCoCrFeNiTi high entropy alloy coating resistant to high temperature oxidation on the surface of γ-TiAl alloy.

[0016] Beneficial effect: The present invention provides a high temperature oxidation resistant coating based on titanium alloy matrix self-diffusion and a preparation method thereof. The AlCoCrFeNiTi high entropy alloy coating prepared based on matrix self-diffusion has a cubic structure and exists in a continuous single FCC solid solution structure ( Figure 3 ); using double glow plasma alloying technology, with AlCoCrFeNi target as sputtering source, bombarding the target with high purity argon gas, the TiAl alloy matrix elements diffuse outward, and prepare AlCoCrFeNiTi high entropy alloy coating resistant to high temperature oxidation on the surface of the matrix; based on the matrix self-diffusion pre-infiltration coating, the mutual diffusion between the matrix and the coating can be improved, and the metallurgical bonding between the pre-infiltration layer and the matrix can be improved; the comprehensive mechanical properties and high temperature oxidation resistance of the coating can be improved; the problem of weak oxidation resistance of γ-TiAl in high temperature environment above 800℃ is solved, and the application range of titanium aluminum alloy is broadened. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic diagram of the structure of the high temperature oxidation resistant coating on the surface of γ-TiAl alloy; Figure 2 Interface morphology of the high-temperature oxidation-resistant AlCoCrFeNiTi high-entropy alloy coating prepared on the surface of the γ-TiAl alloy in Example 1: (a) before oxidation; (b) oxidation at 1000°C for 30h; (c) oxidation at 1000°C for 70h; (d) oxidation at 1000°C for 100h;

[0018] Figure 3 This is the XRD pattern of AlCoCrFeNiTi high entropy alloy coating. DETAILED DESCRIPTION

[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments:

[0020] If no specific conditions are specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0021] The following examples all use γ-TiAl alloy as the matrix to ensure that Ti can diffuse into the coating.

[0022] The AlCoCrFeNiTi high temperature oxidation resistant coating on the surface of γ-TiAl alloy is an AlCoCrFeNiTi coating prepared step by step on γ-TiAl by using double glow plasma alloying technology; Figure 1 As shown in the figure, Al, Co, Cr, Fe, Ni, and Ti elements are deposited on the surface of the TiAl matrix, forming an interdiffusion zone with the matrix, and the coating and the matrix have a metallurgical bond. The AlCoCrFeNiTi anti-oxidation coating is formed on the surface of the titanium-aluminum alloy through matrix self-diffusion, which is expected to solve the problem of weak anti-oxidation performance of γ-TiAl in high-temperature environments above 800°C, and broaden the application range of titanium-aluminum alloys.

[0023] Example 1

[0024] The preparation of the AlCoCrFeNiTi anti-oxidation coating is characterized in that the Ti element in the coating is formed by self-diffusion of the substrate, and comprises the following steps:

[0025] Step 1, base material pretreatment:

[0026] Prepare γ-TiAl alloy, grind it step by step on 180#, 500#, 1500#, and 2000# metallographic sandpaper, polish it with flannel cloth until it has a scratch-free mirror surface, and then ultrasonically clean it in alcohol for later use;

[0027] Step 2: Clean and place the workpiece:

[0028] The γ-TiAl alloy cleaned in step 1 is loaded into the furnace. Before loading, the inner wall of the furnace body and the surface of the target material need to be polished with fine sandpaper, and the surface oxide film and impurities are removed, and then wiped with a dust-free cloth dipped in anhydrous ethanol. The γ-TiAl alloy is used as the cathode, and the AlCoCrFeNi high entropy alloy target is used as the source, wherein the atomic ratio of each element is Al: Co: Cr: Fe: Ni = 1:1:1:1:1;

[0029] Step 3, vacuum:

[0030] Turn on the mechanical pump and open the mechanical pump exhaust valve. When the air pressure is pumped below 10Pa, open the electromagnetic isolation valve. When the air pressure is pumped below 1Pa, turn on the molecular pump to pump the air pressure in the furnace to 1×10-3Pa. Then, introduce argon gas and close the molecular pump and electromagnetic isolation valve.

[0031] Step 4, gas washing:

[0032] Control the Ar flowmeter to adjust the Ar flow rate. On the basis of fully opening the mechanical pump (the mechanical pump is fully opened in the subsequent process, and the air pressure is regulated by controlling the Ar flow rate), raise the air pressure to 100Pa, then reduce the Ar flow rate to 10Pa, repeat this operation three times, and complete the gas washing step;

[0033] Step 5, source and cathode cleaning:

[0034] Turn on the circulating water of the equipment and adjust the gas pressure in the furnace to 20Pa, turn on the cathode power supply, increase it to 600V, and keep it at this voltage for 20 minutes. After the end, turn on the source power supply, increase it to 900V, and keep it warm for 20 minutes. In this process, the bombardment of Ar ions can remove pollutants on the surface of the substrate and target, including oil stains and oxides;

[0035] Step 6, voltage boost process:

[0036] Adjust the gas pressure to below 10Pa, slowly increase the source voltage and cathode voltage to the set voltage, then slowly increase the gas pressure and finally adjust it to the working pressure of 35Pa;

[0037] Step 7, pre-infiltration AlCoCrFeNi process:

[0038] Set the workpiece voltage to 400V, the workpiece voltage to 900V, and adjust the workpiece duty cycle to keep the workpiece temperature at 850℃ for 3h;

[0039] Step 8, vacuum annealing:

[0040] The pre-infiltrated AlCoCrFeNi coating was vacuum annealed for 4 h at 900 °C with argon as the protective gas.

[0041] Step 9, re-infiltration AlCoCrFeNi process:

[0042] After the annealing of the pre-infiltrated AlCoCrFeNi coating was completed, AlCoCrFeNi was infiltrated again. The workpiece voltage was 400V, the target voltage was set to 800V, and the workpiece duty cycle was adjusted to keep the workpiece temperature at 750℃ for 5h.

[0043] Step 10, voltage reduction process:

[0044] Slowly reduce the source and cathode voltages, with the source voltage reduction rate of 10V / min and the cathode voltage reduction rate of 5V / min. The entire voltage reduction process needs to last for more than half an hour. When the voltage drops to a lower value, it can be directly turned off. This process needs to avoid the voltage reduction rate being too fast, which will cause the temperature to drop rapidly and cause greater thermal stress on the coating.

[0045] Example 2

[0046] The preparation of the AlCoCrFeNiTi anti-oxidation coating is characterized in that the Ti element in the coating is formed by self-diffusion of the substrate, and comprises the following steps:

[0047] Step 1, base material pretreatment:

[0048] Prepare γ-TiAl alloy, grind it step by step on 180#, 500#, 1500#, and 2000# metallographic sandpaper, polish it with flannel cloth until it has a scratch-free mirror surface, and then ultrasonically clean it in alcohol for later use;

[0049] Step 2: Clean and place the workpiece:

[0050] The γ-TiAl alloy cleaned in step 1 is loaded into the furnace. Before loading, the inner wall of the furnace body and the surface of the target material need to be polished with fine sandpaper, and the surface oxide film and impurities are removed, and then wiped with a dust-free cloth dipped in anhydrous ethanol. The γ-TiAl alloy is used as the cathode and the AlCoCrFeNi target material is used as the source;

[0051] Step 3, vacuum:

[0052] Turn on the mechanical pump and open the mechanical pump exhaust valve. When the air pressure is pumped below 10Pa, open the electromagnetic isolation valve. When the air pressure is pumped below 1Pa, turn on the molecular pump to pump the air pressure in the furnace to 1×10-3Pa. Then introduce argon gas and close the molecular pump and electromagnetic isolation valve.

[0053] Step 4, gas washing:

[0054] Control the Ar flowmeter to adjust the Ar flow rate. On the basis of fully opening the mechanical pump (the mechanical pump is fully opened in the subsequent process, and the air pressure is regulated by controlling the Ar flow rate), raise the air pressure to 100Pa, then reduce the Ar flow rate to 10Pa, repeat this operation three times, and complete the gas washing step;

[0055] Step 5, source and cathode cleaning:

[0056] Turn on the circulating water of the equipment and adjust the gas pressure in the furnace to 20Pa, turn on the cathode power supply, increase it to 600V, and keep it at this voltage for 20 minutes. After the end, turn on the source power supply, increase it to 900V, and keep it warm for 20 minutes. In this process, the bombardment of Ar ions can remove pollutants on the surface of the substrate and target, including oil stains and oxides;

[0057] Step 6, voltage boost process:

[0058] Adjust the gas pressure to below 10Pa, slowly increase the source voltage and cathode voltage to the set voltage, then slowly increase the gas pressure and finally adjust it to the working pressure of 30Pa;

[0059] Step 7, pre-infiltration AlCoCrFeNi process:

[0060] Set the workpiece voltage to 400V, the workpiece voltage to 900V, and adjust the workpiece duty cycle to keep the workpiece temperature at 850℃ for 5h;

[0061] Step 8, vacuum annealing:

[0062] The pre-infiltrated AlCoCrFeNi coating was vacuum annealed for 4 h at 900 °C with argon as the protective gas.

[0063] Step 9, re-infiltration AlCoCrFeNi process:

[0064] After the annealing of the pre-infiltrated AlCoCrFeNi coating was completed, AlCoCrFeNi was infiltrated again. The workpiece voltage was 400V, the target voltage was set to 800V, and the workpiece duty cycle was adjusted to keep the workpiece temperature at 750℃ for 7h.

[0065] Step 10, voltage reduction process:

[0066] Slowly reduce the source and cathode voltages, with the source voltage reduction rate of 10V / min and the cathode voltage reduction rate of 5V / min. The entire voltage reduction process needs to last for more than half an hour. When the voltage drops to a lower value, it can be turned off directly. This process needs to avoid the voltage reduction rate being too fast, which will cause the temperature to drop rapidly and cause greater thermal stress on the coating.

[0067] Example 3

[0068] The preparation of the AlCoCrFeNiTi anti-oxidation coating is characterized in that the Ti element in the coating is formed by self-diffusion of the substrate, and comprises the following steps:

[0069] Step 1, base material pretreatment:

[0070] Prepare γ-TiAl alloy, grind it step by step on 180#, 500#, 1500#, and 2000# metallographic sandpaper, polish it with flannel cloth until it has a scratch-free mirror surface, and then ultrasonically clean it in alcohol for later use;

[0071] Step 2: Clean and place the workpiece:

[0072] The γ-TiAl alloy cleaned in step 1 is loaded into the furnace. Before loading, the inner wall of the furnace body and the surface of the target material need to be polished with fine sandpaper, and the surface oxide film and impurities are removed, and then wiped with a dust-free cloth dipped in anhydrous ethanol. The γ-TiAl alloy is used as the cathode and the AlCoCrFeNi target material is used as the source;

[0073] Step 3, vacuum:

[0074] Turn on the mechanical pump and open the mechanical pump exhaust valve. When the air pressure is pumped below 10Pa, open the electromagnetic isolation valve. When the air pressure is pumped below 1Pa, turn on the molecular pump to pump the air pressure in the furnace to 1×10-3Pa. Then introduce argon gas and close the molecular pump and electromagnetic isolation valve.

[0075] Step 4, gas washing:

[0076] Control the Ar flowmeter to adjust the Ar flow rate. On the basis of fully opening the mechanical pump (the mechanical pump is fully opened in the subsequent process, and the air pressure is regulated by controlling the Ar flow rate), raise the air pressure to 100Pa, then reduce the Ar flow rate to 10Pa, repeat this operation three times, and complete the gas washing step;

[0077] Step 5, source and cathode cleaning:

[0078] Turn on the circulating water of the equipment and adjust the gas pressure in the furnace to 20Pa, turn on the cathode power supply, increase it to 600V, and keep it at this voltage for 20 minutes. After the end, turn on the source power supply, increase it to 900V, and keep it warm for 20 minutes. In this process, the bombardment of Ar ions can remove pollutants on the surface of the substrate and target, including oil stains and oxides;

[0079] Step 6, voltage boost process:

[0080] Adjust the gas pressure to below 10Pa, slowly increase the source voltage and cathode voltage to the set voltage, then slowly increase the gas pressure and finally adjust it to the working pressure of 35Pa;

[0081] Step 7, pre-infiltration AlCoCrFeNi process:

[0082] Set the workpiece voltage to 400V, the workpiece voltage to 900V, and adjust the workpiece duty cycle to keep the workpiece temperature at 850℃ for 5h;

[0083] Step 8, re-infiltration AlCoCrFeNi process:

[0084] After the annealing of the pre-infiltrated AlCoCrFeNi coating was completed, AlCoCrFeNi was infiltrated again. The workpiece voltage was 400V, the target voltage was set to 800V, and the workpiece duty cycle was adjusted to keep the workpiece temperature at 750℃ for 7h.

[0085] Step 9, voltage reduction process:

[0086] Slowly reduce the source and cathode voltages, with the source voltage reduction rate of 10V / min and the cathode voltage reduction rate of 5V / min. The entire voltage reduction process needs to last for more than half an hour, and it can be turned off directly when the voltage drops to a lower value. In this process, it is necessary to avoid the voltage reduction rate being too fast, which will cause the temperature to drop rapidly and cause greater thermal stress on the coating.

[0087] Comparative Example 1

[0088] Step 1, base material pretreatment:

[0089] Prepare Inconel740 nickel-based alloy, grind it step by step on 180#, 500#, 1500#, and 2000# metallographic sandpaper, polish it with flannel cloth until it has a scratch-free mirror surface, and then ultrasonically clean it in alcohol for later use;

[0090] Step 2: Clean and place the workpiece:

[0091] The Inconel740 nickel-based alloy block cleaned in step 1 is loaded into the furnace. Before loading, the inner wall of the furnace body and the surface of the target material need to be polished with fine sandpaper, and the surface oxide film and impurities are removed, and then wiped with a dust-free cloth dipped in anhydrous ethanol. The Inconel740 alloy is used as the cathode and the AlCoCrFeNi target material is used as the source;

[0092] Step 3, vacuum:

[0093] Turn on the mechanical pump and open the mechanical pump exhaust valve. When the air pressure is pumped below 10Pa, open the electromagnetic isolation valve. When the air pressure is pumped below 1Pa, turn on the molecular pump to pump the air pressure in the furnace to 1×10-3Pa. Then, introduce argon gas and close the molecular pump and electromagnetic isolation valve.

[0094] Step 4, gas washing:

[0095] Control the Ar flowmeter to adjust the Ar flow rate. On the basis of fully opening the mechanical pump (the mechanical pump is fully opened in the subsequent process, and the air pressure is regulated by controlling the Ar flow rate), raise the air pressure to 100Pa, then reduce the Ar flow rate to 10Pa, repeat this operation three times, and complete the gas washing step;

[0096] Step 5, source and cathode cleaning:

[0097] Turn on the circulating water of the equipment and adjust the gas pressure in the furnace to 20Pa, turn on the cathode power supply, increase it to 600V, and keep it at this voltage for 20 minutes. After the end, turn on the source power supply, increase it to 900V, and keep it warm for 20 minutes. In this process, the bombardment of Ar ions can remove pollutants on the surface of the substrate and target, including oil stains and oxides;

[0098] Step 6, voltage boost process:

[0099] Adjust the gas pressure to below 10Pa, slowly increase the source voltage and cathode voltage to the set voltage, then slowly increase the gas pressure and finally adjust it to the working pressure of 35Pa;

[0100] Step 7, pre-infiltration AlCoCrFeNi process:

[0101] Set the workpiece voltage to 400V, the workpiece voltage to 900V, and adjust the workpiece duty cycle to keep the workpiece temperature at 850℃ for 3h;

[0102] Step 8, vacuum annealing

[0103] The pre-infiltrated AlCoCrFeNi coating was vacuum annealed for 4 h at a temperature of 900°C with argon as the protective gas.

[0104] Step 9, re-infiltration AlCoCrFeNi process:

[0105] After the annealing of the pre-infiltrated AlCoCrFeNi coating was completed, AlCoCrFeNi was infiltrated again. The workpiece voltage was 400V, the target voltage was set to 800V, and the workpiece duty cycle was adjusted to keep the workpiece temperature at 750℃ for 5h.

[0106] Step 10, voltage reduction process:

[0107] Slowly reduce the source and cathode voltages, with the source voltage reduction rate of 10V / min and the cathode voltage reduction rate of 5V / min. The entire voltage reduction process needs to last for more than half an hour, and it can be turned off directly when the voltage drops to a lower value. In this process, it is necessary to avoid the voltage reduction rate being too fast, which will cause the temperature to drop rapidly and cause greater thermal stress on the coating.

[0108] The ratios of the elements in the above examples and comparative examples are shown in Table 1:

[0109] Table 1 Element ratios in Examples and Comparative Examples (at.%)

[0110] Al Co Cr Fe Ni Ti Example 1 Deposition layer 19.26 18.53 20.83 19.07 18.05 4.26 Example 1 Diffusion layer 24.18 17.92 16.57 17.82 16.08 7.43 Example 2 Deposition layer 18.42 19.91 19.87 20.88 19.13 1.79 Example 2 Diffusion layer 20.73 18.57 18.41 19.2 17.64 5.45 Example 3 Deposition layer 19.4 21.67 18.96 19.49 19.66 0.82 Example 3 Diffusion layer 18.38 19.96 19.14 20.38 18.33 3.81 Comparative Example 1 Deposition layer 21.7 19.76 19.16 20.15 19.23 -- Comparative Example 1 Diffusion Layer 20.71 18.72 18.92 19.51 22.14 --

[0111] Comparison of high temperature oxidation resistance between Example 1, Example 2 and Example 3 and Comparative Example 1:

[0112] High-temperature oxidation tests were carried out on the AlCoCrFeNiTi high-temperature oxidation resistant coatings prepared under different preparation processes to observe the morphology after oxidation. The specific operations are as follows: three temperatures of 800°C, 900°C and 1000°C were selected, and high-temperature oxidation experiments were carried out on the TiAl substrate samples and the AlCoCrFeNiTi coating samples for 100 hours respectively. According to the test requirements, the substrate and AlCoCrFeNiTi coating samples were numbered, and each parameter was divided into three parallel groups, and placed in a crucible with a lid and placed in a muffle furnace set at different temperatures. Each high-temperature oxidation was performed for 10 hours, and the furnace was cooled to room temperature, the crucible was taken out, and the crucible was weighed together with the crucible, and the weight gain of each sample was analyzed, and the oxidized sample was subsequently tested and analyzed. The results are shown in Table 2. It can be seen from the table that the AlCoCrFeNiTi coating on the surface of the γ-TiAl alloy exhibits good high-temperature oxidation resistance at different temperatures. For the AlCoCrFeNi coating prepared on the Inconel740 nickel-based alloy, its high-temperature oxidation resistance decreased significantly, especially after the oxidation temperature reached 1000°C. Figure 2 As shown, the coating prepared in Example 1 has good antioxidant effect when oxidized at 1000°C for 30 hours; it still maintains good antioxidant properties when oxidized at 1000°C for 70 hours; when oxidized at 1000°C for 100 hours, microscopic holes are produced in the coating and the antioxidant effect decreases.

[0113] The difference between Example 1, Example 2 and Example 3 and Comparative Example 1 is that the comparative example does not infiltrate a high entropy alloy coating on the TiAl alloy. It can be seen that the high-temperature oxidation resistance of the AlCoCrFeNiTi coating based on self-diffusion of the TiAl matrix prepared in Example 1, Example 2 and Example 3 is significantly better than the AlCoCrFeNi coating of the Ni-based alloy in Comparative Example 1; this is because during the oxidation process, the AlCoCrFeNiTi coating generates complex oxides. The oxides generated when oxidized at 800°C are Al2O3, TiO2, Cr2O3 and FeCr2O4, and Fe2TiO5 is newly added when oxidized at 900°C. The oxidation products when oxidized at 1000°C are the simplest, with only three oxidation products, Al2O3, TiO2 and Fe2TiO5. The oxide film generated after oxidation is relatively dense, which can prevent the alloy from being further oxidized and play a certain protective role.

[0114] Table 2 High temperature oxidation resistance time of alloys and samples after coating at different temperatures

[0115]

[0116] In summary, the high-temperature oxidation resistance of Examples 1, 2 and 3 of the present invention is significantly better than that of Comparative Example 1. The preparation method of the embodiments of the present invention mainly includes preparing AlCoCrFeNi coatings distributed on the surface of γ-TiAl by double glow plasma alloying technology. This method is based on the self-diffusion of Ti elements in the matrix to form AlCoCrFeNiTi coatings. The method is simple and can improve the shortcomings of insufficient high-temperature oxidation resistance of the surface of γ-TiAl alloy above 800°C. The coating and the matrix form mutual diffusion, which solves the problem of reduced coating performance caused by mismatch of thermal expansion coefficients between the matrix and the coating. The high entropy alloy coating prepared by the present invention is resistant to oxidation, has high bonding strength and good comprehensive mechanical properties.

[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high temperature oxidation resistant coating based on self-diffusion of a titanium alloy substrate, characterized in that: The following steps are involved: S1: A double glow plasma alloying technology is used to prepare an AlCoCrFeNi pre-infiltration layer on the surface of the γ-TiAl alloy, so that the substrate and the coating can form mutual diffusion to the greatest extent. The technical parameters of the double glow plasma alloying are: the workpiece voltage is set to 400V, and the target voltage is set to 900V; the workpiece duty cycle is adjusted to keep the workpiece temperature at 800℃~1000℃, the holding time is 3h~7h, and the AlCoCrFeNi high entropy alloy target is the source, wherein the atomic ratio of each element is Al:Co:Cr:Fe:Ni=1:1:1:1:1; then the pre-infiltration layer is vacuum annealed at 600℃~900℃ for 2~10 hours to promote the diffusion of coating elements in the γ-TiAl alloy; S2: AlCoCrFeNi was re-infiltrated on the surface of the pre-infiltrated layer after annealing using double glow plasma alloying technology. By changing the workpiece pole and target pole parameters, the controllable diffusion of Ti in the matrix to the coating direction was achieved to prepare the AlCoCrFeNiTi high entropy alloy high temperature oxidation resistant coating. The parameters in the preparation process were: workpiece voltage of 400V, target voltage of 800V; the workpiece duty cycle was adjusted to keep the workpiece temperature at 700℃~900℃, and the holding time was 5h~7h.

2. The method for preparing a high temperature oxidation resistant coating based on self-diffusion of a titanium alloy substrate according to claim 1, characterized in that: In step S1, the workpiece temperature is maintained at 850° C. for 3 h.

3. The method for preparing a high temperature oxidation resistant coating based on self-diffusion of a titanium alloy substrate according to claim 1, characterized in that: The annealing time was 4 hours.

4. The method for preparing a high temperature oxidation resistant coating based on self-diffusion of a titanium alloy substrate according to claim 1, characterized in that: In step S2, the workpiece temperature is maintained at 750° C. for 5 h.

5. The high temperature oxidation resistant coating based on titanium alloy matrix self-diffusion prepared by the method according to any one of claims 1 to 4, characterized in that: The coating is an AlCoCrFeNiTi high entropy alloy coating, which comprises a deposition layer and a diffusion layer from the surface to the inside, and the Ti element in the coating originates from the AlCoCrFeNiTi high entropy alloy coating formed by self-diffusion of a γ-TiAl alloy matrix.

6. The high temperature oxidation resistant coating based on self-diffusion of titanium alloy matrix according to claim 5, characterized in that: The thickness of the deposition layer is 15-25 μm, and the thickness of the diffusion layer is 20-35 μm.

7. The high temperature oxidation resistant coating based on titanium alloy matrix self-diffusion according to claim 5 or 6, characterized in that: The thickness of the deposition layer is 20 μm; the thickness of the diffusion layer is 25 μm.

Citation Information

Cited By

  • High-temperature oxidation resistant high-entropy alloy coating containing second phase reinforcement and preparation method thereof

    CN122214855A

  • An oxidation-resistant layer prepared by niobium infiltration on a titanium alloy surface and a preparation method thereof

    CN122727710A